Numerical Investigation at Lower Stagnation Point Flow Over a Horizontal Circular Cylinder of Brinkman-Viscoelastic Fluid - Siti Farah Haryatie, Mohd Kanafiah; Abdul Rahman, Mohd Kasim; Syazwani, Mohd Zokri; Nur Syamilah, Arifin (Akademi Baru, 2021)
Investigations on the characteristics of fluid flow in manufacturing processes are essential since it will determine the quality of the end products. The flow might be involved whether the Newtonian (viscous) or non-Newtonian fluid moving over the different body depending on the process activities. Since the experimental works sometimes costly and hazardous, the study via mathematical approach is necessary to counter the limitations. Hence, this paper aims to investigate the flow at lower stagnation point over a horizontal circular cylinder on Brinkman Viscoelastic fluid embedded in porous medium. Mathematical model is constructed in terms of partial differential equations with some physical conditions to represent the condition of the problem. An appropriate non-dimensional variable is introduced to transform the model into the solvable system which is in less complexity, and then the system is solved using the Runge-Kutta-Fehlberg method. The numerical solutions for the temperature and velocity profiles as well as skin friction and heat transfer coefficient are computed and presented in graphical and tabular form. The feature of the flow and heat transfer characteristics for various values of mixed convection, Brinkman and viscoelastic parameter are analysed and discussed. This study has found that the incremented Brinkman and viscoelastic parameter have declined the fluid velocity while opposite trend is observed for temperature distribution. The theoretical results produced are relevance to researchers and engineers. It can be used for comparative purposes in data validation or experimentation study.